A comparison of conscious sedation and local anesthesia for thrombectomy in acute ischemic stroke: a multicenter study - Onalan, Aysenur; Gurkas, Erdem; Akpinar, Cetin Kursad; Aykaç, Özlem; Acar, Turkan; Acar, Bilgehan; Kocabaş, Zehra Uysal; Doğan, Hasan; Balgetir, Ferhat; Genc, Sule Kavak; Yabalak, Ahmet; Ozdemir, Atilla Ozcan (Frontiers in Neurology, 2024)
Introduction Ischemic cerebrovascular disease (ICVD) is a serious health problem in which brain tissue suffers from hypoxic damage due to obstruction in cerebral vessels. Mechanical thrombectomy is a commonly used method in the treatment of these patients. However, the effects of local anesthesia (LA) and conscious sedation (CS) during thrombectomy are still unclear. We evaluated whether there was a relationship between both anesthesia regimens in terms of 90-day mRS scores. Methods In this study, a retrospective observational study was conducted to evaluate the effects of local anesthesia and conscious sedation used during mechanical thrombectomy in 4 comprehensive stroke centers among ICVD patients. Patients were divided into the LA group and the CS group. Statistical analysis was made both before and after 1:1 matching under propensity score matching (PSM) analysis. primary outcome measure was mRS score of 0–2 at 90 days. Secondary outcomes were procedure times, recanalization rates, symptomatic and asymptomatic hemorrhage rates, and procedural complications. Results A total of 193 patients (118 patients with LA and 75 patients with CS) were included in the final analysis before propensity score matching. After 1:1 propensity score matching, 98 patients—49 patients from each group—were included in the study. There was no difference in clinical outcome between LA and CS-applied groups (p = 0.543). When blood pressure values at follow-up after endovascular treatment were compared, the lowest systolic and lowest diastolic blood pressures were found to be lower in the CS group (respectively, p = 0.001, p = 0.009). There was no significant difference between the two groups in terms of recanalization rates, symptomatic incranial hemorrhage (sICH) rates, 90-day mRS, and procedure-related complication rates (respectively, p = 0.617, p = 0.274, p = 0.543, and p = 1.000). Conclusion This study did not reveal the superiority of CS applied during endovascular treatment on 90-day mRS, sICH, recanalization rates, or procedural complications. However, the risk of developing hypotension during the CS application was found to be high.